Sistem Akuntansi Penerimaan dan Pengeluaran Kas PT Mitra Usaha Harta Gemilang Tanjung Priok - Sakti Muda Nasution; Nizar Nurzaman (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
Cash is a current asset that is easily transferable. For this reason, a cash accounting information system is needed that regulates cash receipts and disbursements designed so that each transaction flow related to cash can be recorded properly. The purpose of this research is to describe the cash receipts and disbursements of PT Mitra Usaha Harta Gemilang Tanjung Priok Branch. The object of research is the accounting system for cash receipts and disbursements at PT Mitra Usaha Harta Gemilang. The results showed that the cash receipts and disbursement system of PT Mitra Usaha Harta Gemilang Tanjung Priok Branch has been running effectively and according to existing procedures, namely there is authorization for transactions that occur from the authorities, there is a separation of functions and has a good internal control system.